2017
DOI: 10.1002/chem.201703938
|View full text |Cite
|
Sign up to set email alerts
|

Bimetallic Co‐Mn Perovskite Fluorides as Highly‐Stable Electrode Materials for Supercapacitors

Abstract: Bimetallic Co-Mn perovskite fluorides (KCo Mn F , denoted as K-Co-Mn-F) with various Co/Mn ratios (1:0, 12:1, 6:1, 3:1, 1:1, 1:3, 0:1) were prepared through a one-pot solvothermal strategy and further used as electrode materials for supercapacitors. The optimal K-Co-Mn-F candidate (Co/Mn=6:1) showed a size range of 0.1-1 μm and uniform elemental distribution; exhibiting small changes in XRD peaks and XPS binding energy in comparison to the bare K-Co-F and K-Mn-F, due to the structural/electronic effects. Owing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 52 publications
(16 citation statements)
references
References 34 publications
(93 reference statements)
0
16
0
Order By: Relevance
“…Specifically, the three typical diffraction peaks of the LSCFO catalyst located at 33.1, 47.5, and 58.9° can be accurately indexed into (110), (024), and (214) facets of standard LaCoO 3 (PDF# 48-0123), respectively. It is worth noting that the main diffraction peak assigned to the (110) crystal facet of LSCFO shows a slight shift toward a small 2θ angle in comparison with the initial LCO sample (Figure c), which was attributed to the partial replacement of La and Co ions in the LCO sample by Sr and Fe cations with different ionic radii . In addition, to further prove the successful doping of Sr and Fe, the Rietveld-refined XRD patterns and the obtained crystallographic parameters of the LSCO, LCFO, LSCFO, and original LCO are displayed in Figure d and Table S1.…”
Section: Resultsmentioning
confidence: 89%
“…Specifically, the three typical diffraction peaks of the LSCFO catalyst located at 33.1, 47.5, and 58.9° can be accurately indexed into (110), (024), and (214) facets of standard LaCoO 3 (PDF# 48-0123), respectively. It is worth noting that the main diffraction peak assigned to the (110) crystal facet of LSCFO shows a slight shift toward a small 2θ angle in comparison with the initial LCO sample (Figure c), which was attributed to the partial replacement of La and Co ions in the LCO sample by Sr and Fe cations with different ionic radii . In addition, to further prove the successful doping of Sr and Fe, the Rietveld-refined XRD patterns and the obtained crystallographic parameters of the LSCO, LCFO, LSCFO, and original LCO are displayed in Figure d and Table S1.…”
Section: Resultsmentioning
confidence: 89%
“…Previous density functional theory (DFT) studies showed that the substitution of F for O in Fe 2 O 3 improves electrical conductivity because of the generation of defect levels and the decreased band gap after F dopants, thereby facilitating the reaction kinetics of Fe 2 O 3 toward a photoelectrochemical processes [16]. In addition, the highly ionic nature of the metal-fluorine bond that can provide higher lattice energy and suppress the polarization with respect to their oxide counterparts, and thus increases redox M A N U S C R I P T A C C E P T E D ACCEPTED MANUSCRIPT 4 potential of electrode materials [17,18]. On the other hand, the intentional creation of O vacancies in the lattice of transition metal oxides has been proven as an effective approach to increase the reactivity of electrochemically active sites and to modify electrical properties [19,20], which are beneficial to enhancement of electrochemical performance.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…It has been reported that transition element based perovskite fluorides acted as potential electrode materials for rechargeable batteries 7,8 , where perovskite structure provide the robust architecture with intersectional tetragonal cavity chains 9 . Based on the above considerations, the bimetallic Co-Mn-based perovskite fluorides has been reported for the advanced electrode materials for supercapacitor application by exploiting the synergistic effect of Co and Mn redox species 10 . Though metal fluorides are insulator in nature and cannot be used as conventional electrode materials for device architecture, but at the lower voltage condition, microstrutured metal fluorides have been shown reversible reactivity 11 .…”
mentioning
confidence: 99%